Agricultural Pesticide Sprayers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Volume 1. FAO Guidelines on Equipment Quality Control and Use and FAO Minimum Standards. FAO. 1998. 32 pp.ISBN 925 104118 0.Volume 2. FAO Technical Standards: Sprayer Specifications and Test Procedures. FAO. 1998. 63 pp.ISBN 92 5 104119 9.$11.00...